2018
DOI: 10.1038/s41594-018-0030-z
|View full text |Cite
|
Sign up to set email alerts
|

2′-O-methylation in mRNA disrupts tRNA decoding during translation elongation

Abstract: Chemical modifications of messenger RNA (mRNA) may regulate many aspects of mRNA processing and protein synthesis. Recently, 2′-O-methylation of nucleotides was identified as a frequent modification in translated regions of human mRNA, showing enrichment in codons for certain amino acid. Here, using single-molecule, bulk kinetics and structural methods, we show that 2′-O-methylation within coding regions of mRNA disrupts key steps in codon reading during cognate transfer RNA (tRNA) selection. Our results sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
90
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 43 publications
7
90
0
1
Order By: Relevance
“…Analysis of 441 smFRET traces indicated three classes of translation events ( Fig 4E): Complete translation of ORF (54%), aborted translation after 4 th amino acid (G 4 ) without Lys-(Cy5)-tRNA Lys sampling (defined as tRNA binding longer than >100 millisecond 48 the A-site Lys codon (45%), and one that exhibited Lys-(Cy5)-tRNA Lys sampling in aborted translation (1%). Considering that a majority of arrested ribosomes exhibited a non-rotated-like conformational state without (>100ms lifetime) A-site tRNA sampling necessary for a processive elongation, we hypothesize that the ribosome is in a non-canonical structural state that cannot make a stable interaction among rRNA monitoring bases and codon-anticodon duplex necessary for further elongation 48 . Such state may be a result of different pathing of an mRNA as well as a nascent-peptide molecule within the ribosome, possibly similar to the previously observed interaction among the ErmCL nascent-peptide, the ribosome exit tunnel and the antibiotic erythromycin 49 .…”
Section: Mainmentioning
confidence: 99%
“…Analysis of 441 smFRET traces indicated three classes of translation events ( Fig 4E): Complete translation of ORF (54%), aborted translation after 4 th amino acid (G 4 ) without Lys-(Cy5)-tRNA Lys sampling (defined as tRNA binding longer than >100 millisecond 48 the A-site Lys codon (45%), and one that exhibited Lys-(Cy5)-tRNA Lys sampling in aborted translation (1%). Considering that a majority of arrested ribosomes exhibited a non-rotated-like conformational state without (>100ms lifetime) A-site tRNA sampling necessary for a processive elongation, we hypothesize that the ribosome is in a non-canonical structural state that cannot make a stable interaction among rRNA monitoring bases and codon-anticodon duplex necessary for further elongation 48 . Such state may be a result of different pathing of an mRNA as well as a nascent-peptide molecule within the ribosome, possibly similar to the previously observed interaction among the ErmCL nascent-peptide, the ribosome exit tunnel and the antibiotic erythromycin 49 .…”
Section: Mainmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] Modified nucleotides in tRNA, rRNAa nd mRNAd on ot only affect RNAp rocessing,t ransport and stability,b ut these residues also impact mRNAt ranslation. [11][12][13][14][15] Despite these important findings,d etails are scarce and disputed on the distribution and functions of many modified nucleotides in different transcriptomes.O nly recently,h igh-throughput sequencing (NGS) methods coupled to antibody-directed enrichment provided comprehensive maps of m 6 Aa nd m 1 A residues in different species. [16][17][18] Foro ther RNAm odifications,the use of specific chemical reagents allowed their highthroughput mapping.…”
mentioning
confidence: 99%
“…The entire function of 2'-O-methylation remained unclear, which was limited to a research tool. The previous study suggested that Nm seemed to involved in immune response via mRNA 5' cap Nm sites, mRNA alternative splicing mediated by intron branch point, maintaining the secondary structure of rRNA, and regulating protein translation by interfering tRNA-mRNA or mRNA-rRNA interactions [5,6,11,14,21]. Based on our preliminary data shown in this article, the roles of Nm sites in cells were much more prevalent than we expected.…”
Section: Discussionmentioning
confidence: 55%